Making risk management work : engaging people to identify, own and manage risk - Murray-Webster, Ruth; Pullan, Penny (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Making risk management work means engaging people to identify, own and manage risk. Many organisations have spent considerable time and money setting up risk frameworks, processes and supporting tools, but these have failed to deliver value. Instead, focus on the people. Bringing together the expertise of Ruth Murray-Webster in the human aspects of risk management, and Penny Pullan's deep expertise in facilitation, creative collaboration and virtual leadership, the book provides tried and tested approaches to make each process step work well within the context of your own organisation, as well as a guide as to how to work effectively with groups. Through translating a highly technical and complex subject into an easy-to-follow guide, the book goes beyond 'tick-box' approaches and provides top tips on how to engage others in developing risk management solutions and how to avoid many of the common pitfalls. This new edition includes two brand new chapters, one taking a deeper dive into the common decision biases amongst groups in organisations, and one looking at remote and hybrid ways of communication and facilitation. If you are involved in trying to make risk management work, whatever the context, this book will provide you with support and practical advice, in an approachable way, supported by real-life examples and memorable illustrations"--
OCLC-licensed vendor bibliographic record.
Keywords: Risk management; BUSINESS & ECONOMICS / Insurance / Risk Assessment & Management